Kinerja Karyawan Berdasarkan Keterbukaan terhadap Pengalaman, Organizational Citizenship Behavior dan Budaya Organisasi - Satwika, Pratista Arya; Himam, Fathul (Jurnal Psikologi, 2014)
Globalization era demands high organization’s performance to survive. There are some human resource problems in Indonesia that indirectly influence individuals’ performance in the organization. This research aimed to determine openness to experience, organiza¬tional citizenship behavior (OCB) and employee-oriented organizational culture as employee per-formance predictor. Ths was a field study that used a quantitative methodology. A questionnaire was used to collect data about open¬ness to experience, organizational citizenship behavior, employee-oriented organizational culture, and employee performance. Hypothesis test done with regression analysis toward 166 respondents resulted in the value of F=52,971 (p